Design and Fabrication of Jig and Fixture for Milling Operations in the Manufacturing Sector - Indrawan, Rizal; Purnomo, Dhika Aditya; Bisono, Fipka; Karuniawan, Bayu Wiro; Fajardini, Ridhani Anita (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Fixtures and jigs are work-holding devices used to position and support workpieces. Fixtures and jigs are important tools in production because their use determines the performance of the entire production process of a product. There are still situations in the manufacturing sector where products manufactured could be more precise. Work-holding devices that facilitate the machining process must be developed to ensure that the final products satisfy the required criteria. This study aimed to design, manufacture, and evaluate fixtures and jigs and then assess how well they worked with test specimens in rectangular shapes. The jigs and fixtures are planned based on a vacuum table that is adjusted to the machining position on the side of the material. The intention of employing a vacuum system is to simplify the process of setting up the workpiece. Fusion360 Design Software was utilized to design fixtures and jig models. Since aluminum is easy to form and has high wear resistance, it was chosen as the workpiece material. CNC machine was employed in the manufacturing process. Testing of jig and fixture tools is carried out on the side of the test specimen. According to the study's findings, jigs and fixtures accelerate the milling process on the material side. When jigs and fixtures are used, the milling process proceeds 17.47 minutes. Using this jig and fixture makes it possible to shorten the operating time, making the milling process run more quickly. Furthermore, the final product has remarkable dimensional accuracy.